Platelet transfusion in pediatric palliative care: at home or in the hospital? (Paliativní medicína, 2021)
A case study illustrating the issue of transfusion in home care. The curative treatment of the relapse of acute myeloid leukemia in a five years old boy was terminated because of treatment failure. The palliative care team considered giving platelet transfusion to the child either at home or in the nearest hospital. Pros and cons were evaluated in the view of the new guidelines on transfusions to palliative care patients in home care.
Keywords: pediatric palliative care; platelet transfusion